HUBUNGAN KECERDASAN EMOSIONAL TERHADAP PENYESUAIAN DIRI PADA SISWA KELAS XI DI MAN KOTA BINJAI - Nun Zairina (Universitas Islam Negeri Sumatera Utara Medan, 2021)
Abstrak: Adjustment is a process of dynamics that occurs continuously that aims to change an attitude that is useful to get a more harmonious relationship between himself and his environment. The purpose of this study is to explore in depth data about the Relationship of Emotional Intelligence to Self-Adjustment in Students seeks to describe the findings of research and determine the facts with observation instruments, questionnaires, interviews and documentation. As for the informants in this study were the Principal, Deputy Principal, Bk Teachers and students of MAN Kota Binjai. The conclusion from this study can be explained that the Relationship of Emotional Intelligence to Self-Adjustment in Class XI Students in MAN Kota Binjai showed 20% emotional intelligence variable had low emotional intelligence, 60% had moderate emotional intelligence and the remaining 20% had high emotional intelligence. Whereas the 13% adjustment variable had a high adjustment, 57% had a moderate adjustment and 30% had a low adjustment. From the results of the analysis it can be said that the positive correlation between emotional intelligence and self-adjustment in class XI students at MAN Kota Binjai is equal to 0.855. It can be seen that P = 0.855> 0.05. Then there is a significant relationship between emotional intelligence and self-adjustment in class XI students at MAN Kota Binjai, with the nature of a positive relationship where the higher the level of emotional intelligence, the higher the level of adjustment itself. Keywords: Emotional Intelligence, Self-Adjustment.